Doprinos dr. S. Lavića sociologijskoj enciklopedistici / Dr. S. Lavić's Contribution to Sociological encyclopaedic : (Prilog diskusiji o "Leksikonu socioloških pojmova", dr. S. Lavića) / (Contribution to discussion on Dr. S. Lavić's "Lexicon of Sociological Terms") (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
The text deals with Dr. S. Lavić's Contribution to Sociological encyclopaedic.